2023
DOI: 10.1002/cssc.202202265
|View full text |Cite
|
Sign up to set email alerts
|

Basal Plane‐Activated Boron‐Doped MoS2 Nanosheets for Efficient Electrochemical Ammonia Synthesis

Abstract: Under the dual pressure of energy crisis and environmental pollution, ammonia (NH3) is an indispensable chemical product in the global economy. The electrocatalytic synthesis of NH3 directly from nitrogen and water using renewable electricity has become one of the most attractive and important topics. Basal plane‐activated boron‐doped MoS2 nanosheets (B−MoS2) as a non‐noble metal catalyst with excellent performance for N2 electroreduction are synthesized by a facile one‐step hydrothermal method. In 0.1 m Na2SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Apart from that, the intrinsic semiconducting nature of main group elements shows sluggish electronic conductivity which further restricts HER process as it is highly dependent on surface electrons availability [109]. In this regard, Chen et al [110] demonstrated that boron doping onto the basal Boron and nitrogen were co-doped into biomass carbon leading to the generation of pyridinic-N and BC 2 O acting as active site for NRR as investigated by Tian et al [111] with the ammonia production rate of 41 µg h −1 mg −1 cat at −1 V vs RHE. XPS analysis data showed gradual shifting in the binding energy of boron and nitrogen depicting about synergism occurring between boron and nitrogen centers producing sufficient charge density for NRR process.…”
Section: D-block and P-block Heteroatom Dopingmentioning
confidence: 99%
“…Apart from that, the intrinsic semiconducting nature of main group elements shows sluggish electronic conductivity which further restricts HER process as it is highly dependent on surface electrons availability [109]. In this regard, Chen et al [110] demonstrated that boron doping onto the basal Boron and nitrogen were co-doped into biomass carbon leading to the generation of pyridinic-N and BC 2 O acting as active site for NRR as investigated by Tian et al [111] with the ammonia production rate of 41 µg h −1 mg −1 cat at −1 V vs RHE. XPS analysis data showed gradual shifting in the binding energy of boron and nitrogen depicting about synergism occurring between boron and nitrogen centers producing sufficient charge density for NRR process.…”
Section: D-block and P-block Heteroatom Dopingmentioning
confidence: 99%
“…They implied suitable NASICON electrolyte design for SIBs. 272 Yildirim and co-workers also collected 1227 data points from 335 published papers and applied for random forest (for discharge capacity prediction) and decision tree (classification). 271 Chao et al describes the different carbon-based material as anode for sodium battery.…”
Section: Machine Learning On Sodium Batterymentioning
confidence: 99%
“…fabricated the CoS 2 /CeO 2 /Ti composites through a facile method, which showed a high NH 3 yield rate of 3.33 × 10 −10 mol s −1 cm −2 in 0.1 m Na 2 SO 4 . [ 297 ] Moreover, the FeS 2 /MoS 2 /reduced graphene oxide composites, [ 298 ] the Bi 2 S 3 /MoS 2 composites, [ 299 ] the boron doped MoS 2 composites, [ 300 ] the CoS 2 /MoS 2 composites, [ 301 ] the MoS 2 /Mo 2 C composites, [ 302 ] the Au/MoS 2 composites, [ 303 ] the S‐rich MoS 2 composites, [ 304 ] the different types of transition metal (Co, Fe, Cu, Zn, Ni) doped ReS 2 composites, [ 305 ] etc., have been developed as advanced electrocatalysts for NRR. Table 5 summary of the LMCs‐based composites for NRR.…”
Section: Energy Conversion Applicationsmentioning
confidence: 99%